2020
DOI: 10.3389/fpubh.2019.00418
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Particulate Matter From Smoker Homes Induces Bacterial Growth, Biofilm Formation, and Impairs Airway Antimicrobial Activity. A Pilot Study

Abstract: Background: Particulate matter (PM) air pollution causes deleterious health effects; however, less is known about health effects of indoor air particulate matter (IAP). Objective: To understand whether IAP influences distinct mechanisms in the development of respiratory tract infections, including bacterial growth, biofilm formation, and innate immunity. Additionally, we tested whether IAP from Iowa houses of subjects with and without recent respiratory exacerbations recapitulated the National Institute of Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…It is established that ASL can be antimicrobial, and this is often mediated by AMPs [ 1 , 2 , 4 ]. Our findings are the first to demonstrate that primary human airway ASL significantly inactivates CoV-229E and SARS-CoV-2 in vitro ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is established that ASL can be antimicrobial, and this is often mediated by AMPs [ 1 , 2 , 4 ]. Our findings are the first to demonstrate that primary human airway ASL significantly inactivates CoV-229E and SARS-CoV-2 in vitro ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
“…After informed written consent was obtained, human donor lungs, confirmed with polymerase chain reaction to be negative for SARS-CoV-2 infection at the time of tissue retrieval, were dissected to obtain bronchial and tracheal cells. Cells were seeded onto collagen-coated filters at the air-liquid interface by the University of Iowa (UI) Cell Culture Core Repository and then washed to obtain endogenous ASL (n>4 donors/experiment), as described elsewhere [ 4 ]. For donor demographics see Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioluminescent S . aureus (Xen29, Caliper Lifesciences Bioware®) sub-cultured to log-phase growth was suspended in minimal media (5% TSB) and challenged (1:1) by ASL from calcitriol supplemented hAECs and by un-supplemented hAEC ASL [ 25 ]. Briefly, ASL was collected by serially washing (20 μl/well DI H 2 0) hAEC apical surfaces from paired donor cells (n = 4 per experiment), after which media was changed back to baseline media for a >72h washout period.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary results suggest higher adverse effects of outdoor air pollution on cognitive function in women, indicating specific actions for prevention and intervention. Stapleton et al (2020) reported on a pilot study in 21 homes selected from the NIH funded cohort residing in Iowa of current and former smokers, with and without a history of respiratory exacerbations. The aim of the research was at assessing whether indoor air particulate collected from their homes would affect in vitro bacterial growth, biofilm formation, and primary human airway surface liquid antimicrobial activity, identifying mechanisms in the development of respiratory tract infections, including bacterial growth, biofilm formation, and innate immunity.…”
Section: Air Qualitymentioning
confidence: 99%